2008
DOI: 10.1038/nature07021
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 and TGF-β are required for differentiation of human TH17 cells

Abstract: The recent discovery of CD4 + T cells characterized by secretion of interleukin (IL)-17 (T H 17 cells) and the naturally occurring regulatory FOXP3 + CD4 T cell (nT reg ) has had a major impact on our understanding of immune processes not readily explained by the T H 1/T H 2 paradigm. T H 17 and nT reg cells have been implicated in the pathogenesis of human autoimmune diseases, including multiple sclerosis, rheumatoid arthritis, inflammatory bowel disease and psoriasis 1,2 . Our recent data and the work of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
703
10
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 846 publications
(752 citation statements)
references
References 14 publications
32
703
10
7
Order By: Relevance
“…Furthermore, in a study of patients with genetic traits affecting TGF-b, IL-1, IL-6 and IL-23 production, enhanced TGF-b responses, due to mutations in TGFB1 and TGFBR2, did not alter expression of Th17 cells, whereas mutations in STAT3 and IL-12RB1 impaired dedifferentiation or expansion of Th17 cells in vivo [54]. Three recent reports have demonstrated that TGF-b does have a role in promoting differentiation of human Th17 cells in vitro and that previous failures to identify a role for TGF-b reflected the high content of this cytokine in fetal bovine or human serum used to culture the T cells [53,55,56]. It appears that high concentrations of TGF-b, such as that present in FCS can inhibit Th17 differentiation, but that lower concentrations may promote it.…”
Section: Differentiation and Expansion Of Il-17-secreting Cd4 1 T Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, in a study of patients with genetic traits affecting TGF-b, IL-1, IL-6 and IL-23 production, enhanced TGF-b responses, due to mutations in TGFB1 and TGFBR2, did not alter expression of Th17 cells, whereas mutations in STAT3 and IL-12RB1 impaired dedifferentiation or expansion of Th17 cells in vivo [54]. Three recent reports have demonstrated that TGF-b does have a role in promoting differentiation of human Th17 cells in vitro and that previous failures to identify a role for TGF-b reflected the high content of this cytokine in fetal bovine or human serum used to culture the T cells [53,55,56]. It appears that high concentrations of TGF-b, such as that present in FCS can inhibit Th17 differentiation, but that lower concentrations may promote it.…”
Section: Differentiation and Expansion Of Il-17-secreting Cd4 1 T Cellsmentioning
confidence: 99%
“…Three recent reports have demonstrated that TGF-b does have a role in promoting differentiation of human Th17 cells in vitro and that previous failures to identify a role for TGF-b reflected the high content of this cytokine in fetal bovine or human serum used to culture the T cells [53,55,56]. It appears that high concentrations of TGF-b, such as that present in FCS can inhibit Th17 differentiation, but that lower concentrations may promote it.…”
Section: T-cell Subtypes That Secrete Il-17mentioning
confidence: 99%
See 3 more Smart Citations